A Note on Quotient Reflective Subcategories of O-REL. (23rd June 2022) - Qasim, Muhammad; Aslam, Ch. Muhammad Afaq
Abstract : In this paper, we examine the category of ordered-RELspaces. We show that it is a normalized and geometric topological category and give the characterization of local T ¯ 0, local T 0 ′, and local T 1 ordered-RELspaces. Furthermore, we characterize explicitly several notions of T 0 's and T 1 objects in O-REL and study their mutual relationship. Finally, it is shown that the category of T 0 's (resp. T 1 ) ordered-RELspaces are quotient reflective subcategories of O-REL .